The Heath Formation and its role as a Source Rock of the hydrocarbon entrapments of the Tumbes basin - Valencia Cárdenas, Kiko Harold (2021)
The evaluation of the geochemical characteristics of the Heath Formation from the Tumbes basin was performed in order to evaluate its role as the main Source Rock of the trapments discovered in this basin. A total of 84 samples were used between drilling cuttings and outcrop samples. The amount of organic matter present indicates a source rock classification from fair to good, with a statistical representative TOC value of 0.93% (Mean). The organic matter quality is mainly Type II and III kerogens, therefore, they can generate both liquid and gaseous hydrocarbons. The state of thermal maturity, in general suggests that, in the sampled areas, the Heath Fm. is yet immature, except for two samples from offshore wells, which is consistent with geological and geophysical information that point towards the presence of better maturity conditions in deeper zones of the basin, such as the offshore áreas from the coasts of towns of Cancas and Tumbes. On the other hand, the comparison of biomarkers of a representative oil from the north of the Talara basin and two rock extracts from the south of the Tumbes basin indicate a homogeneous correlation, which is accepted as a positive Oil-Mother Rock correlation.